Catalyst Stability Benchmarking for the Oxygen Evolution Reaction: The Importance of Backing Electrode Material and Dissolution in Accelerated Aging Studies. Issue 21 (17th October 2017) - Geiger, Simon; Kasian, Olga; Mingers, Andrea M.; Nicley, Shannon S.; Haenen, Ken; Mayrhofer, Karl J. J.; Cherevko, Serhiy
Abstract: In searching for alternative oxygen evolution reaction (OER) catalysts for acidic water splitting, fast screening of the material intrinsic activity and stability in half‐cell tests is of vital importance. The screening process significantly accelerates the discovery of new promising materials without the need of time‐consuming real‐cell analysis. In commonly employed tests, a conclusion on the catalyst stability is drawn solely on the basis of electrochemical data, for example, by evaluating potential‐versus‐time profiles. Herein important limitations of such approaches, which are related to the degradation of the backing electrode material, are demonstrated. State‐of‐the‐art Ir‐black powder is investigated for OER activity and for dissolution as a function of the backing electrode material. Even at very short time intervals materials like glassy carbon passivate, increasing the contact resistance and concealing the degradation phenomena of the electrocatalyst itself. Alternative backing electrodes like gold and boron‐doped diamond show better stability and are thus recommended for short accelerated aging investigations. Moreover, parallel quantification of dissolution products in the electrolyte is shown to be of great importance for comparing OER catalyst feasibility. Abstract : Ir‐black in back : Fast screening of the material intrinsic activity and stability profiles for acidic oxygen evolution reaction catalysts are of vital importance, but conclusions on the catalyst stability are commonly drawn on the basis of electrochemical information alone. Herein important limitations of such approaches, which are related to the degradation of the backing electrode material, are demonstrated. Ir‐black catalysts are investigated for OER activity and the dissolution behavior is found to depend on the backing electrode material used.